Marketing Activity as a Means of Increasing the Level of International Competitiveness of the Enterprise «Greenpower-Pro» LLC - Proskurnina Nadiia V.; Yeresko Dmytro O. (Bìznes Inform, 2020)
The article is aimed at studying the process of ensuring international competitiveness and increasing its level by forming a marketing complex focused on the appropriate task. The essence of the concept of competitiveness is considered, the factors of competitiveness of enterprise are defined. A strong relationship between the level of international competitiveness of enterprise and the effectiveness of its marketing activities is determined. As a result, upon on the basis of these factors, the main methods of assessing the level of competitiveness of enterprise are identified, based on the analysis of indicators belonging to the marketing activity of enterprise. The assessment of the level of competitiveness of enterprise is carried out by the method based on the theory of effective competition elaborated by Joseph Schumpeter. It is found that the competitiveness of «Greenpower-Pro» LLC is at a high level relative to industry competitors. Since it is determined that the key factors of competitiveness formation are indicators of the effectiveness of the marketing activity of the enterprise, on the basis of these observations, a marketing strategy for increasing the level of competitiveness is built, as well as a balanced system of marketing performance indicators focused on increasing the competitiveness of enterprise is proposed. Measures to implement the proposed balanced system of indicators of marketing activity are defined. The main recommendations for improving marketing activity as an instrument to increase the level of international competitiveness of the production enterprise on the example of «Greenpower-Pro» LLC are formed.